Malay reserve land area trend in district of Johor Bahru, Johor - Ahmad Fuad Ab. Kadir, 1995-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2018